Systemic inflammatory response syndrome and sepsis - epidemiology, differentiation, diagnostics in in clinical practice - Monika Suchomska; Waldemar Halota; Anita Olczak (Kazimierz Wielki University, 2019)
Bacterial infection is an important factor causing morbidity and mortality in different populations. Every time exacerbation of infectious response (strength, time of symptom severity, time of progression) and whole cascade of inflammatory reaction is dependent on the efficiency of the organism's homeostasis. In many situations, especially in case of patients with a decrease level of immune system efficiency, we observe very dynamic intensification of infection and inflammation symptoms. Every time the inflammatory response affect whole body functions and manifests itself in change of biochemical, hematological, and immunological parameters. Those changes are visible specially during systemic inflammatory response. SIRS (systematic inflammatory response syndrome) and sepsis with high levels of incidence and mortality from many years it is a the large diagnostic and therapeutic problem in clinical practice. Annual mortality caused by sepsis which reaches 30 and 50 deaths per 100 000 population, makes it classified as one of a top causes of death among patients under hospital care. Due to its dynamic nature of its course, it is necessary to thoroughly understand its course which may contribute to the search for more effective biochemical and hematological diagnostic markers which will allow to shorten the time of implementation of effective therapy and decrease mortality. The aim of this study was to present the specifity of a SIRS and sepsis and to show its progression, complications and available tools and methods of its diagnosis in clinical practice.